Number and location of mouse mammary tumor virus proviral DNA in mouse DNA of normal tissue and of mammary tumors. - Groner, B (1980)
The Southern DNA filter transfer technique was used to characterize the genomic location of the mouse mammary tumor proviral DNA in different inbred strains of mice. Two of the strains (C3H and CBA) arose from a cross of a Bagg albino (BALB/c) mouse and a DBA mouse. The mouse mammary tumor virus-containing restriction enzyme DNA fragments of these strains had similar patterns, suggesting that the proviruses of these mice are in similar genomic locations. Conversely, the pattern arising from the DNA of the GR mouse, a strain genetically unrelated to the others, appeared different, suggesting that its mouse mammary tumor proviruses are located in different genomic sites. The structure of another gene, that coding for beta-globin, was also compared. The mice strains which we studied can be categorized into two classes, expressing either one or two beta-globin proteins. The macroenvironment of the beta-globin gene appeared similar among the mice strains belonging to one genetic class. Female mice of the C3H strain exogenously transmit mouse mammary tumor virus via the milk, and their offspring have a high incidence of mammary tumor occurrence. DNA isolated from individual mammary tumors taken from C3H mice or from BALB/c mice foster nursed on C3H mothers was analyzed by the DNA filter transfer technique. Additional mouse mammary tumor virus-containing fragments were found in the DNA isolated from each mammary tumor. These proviral sequences were integrated into different genomic sites in each tumor.